2019
DOI: 10.1186/s12913-019-3881-z
|View full text |Cite
|
Sign up to set email alerts
|

What do patients really want? An in-depth examination of patient experience in four Australian hospitals

Abstract: BackgroundPatient satisfaction is an important outcome measure guiding quality improvement in the healthcare setting while the patient-centred care movement places increasing importance on patient engagement in clinical decision-making. However, the concept of patient satisfaction is not clearly defined, and beliefs of patients are not always evident in health surveys. Researchers rarely follow up on surveys to explore patient views and what they mean in greater depth. This study set out to examine perceptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 19 publications
7
57
0
1
Order By: Relevance
“…Healthcare service quality is the essence of hospital development and a key factor influencing patient loyalty 1–3. Traditionally, from a healthcare supplier’s perspective, professional service skills and advanced technology were regarded as key factors to improve healthcare service quality 4.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthcare service quality is the essence of hospital development and a key factor influencing patient loyalty 1–3. Traditionally, from a healthcare supplier’s perspective, professional service skills and advanced technology were regarded as key factors to improve healthcare service quality 4.…”
Section: Introductionmentioning
confidence: 99%
“…Patients are the receivers of healthcare services, and patients’ experiences are one of the most common indicators used to evaluate the quality of healthcare services 2 6 8–10. As an integral component of healthcare quality, patient experience includes several aspects of healthcare delivery that patients value highly when they seek and receive care; for example, timely appointments, easy access to information and good communication with healthcare providers 1 11 12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our other findings about what affects the patient and caregiver experience in the transition from hospital to home are generally in keeping with other studies. Like our study, qualitative work in other jurisdictions has highlighted the importance of compassion and empathy from the health team,40 43 collaborative discharge planning,21 40 41 43–45 caregiver involvement in discharge planning,40 43 and clear, actionable instructions about how to follow-up with concerns once discharged 6 43 46. A large qualitative study conducted at multiple academic centres in the USA concluded that future transitions interventions should focus on enhancing patient self-management and provision of clinical and social support after discharge 6.…”
Section: Discussionmentioning
confidence: 54%
“…Although the role of the patient in the healthcare process is gaining a growing interest, little research has focused on the patient healthcare experience [8,9]. Experiential theorists consider experience as a multidimensional construct that includes cognitive, emotional, social, sensorial and behavioral responses in any direct or indirect interaction with the organization ( [10,11,12].…”
Section: Introductionmentioning
confidence: 99%